Direct Observation of Procedural Skills (DOPS) in Forensic Learning: Usefulness, Disadvantages, Challenges, and Implementation Process - Parmar, Pragnesh; Parekh, Utsav; Gupta, Sanjay (Journal of Forensic Medicine and Toxicology, 2025)
Direct Observation of Procedural Skills (DOPS) is an integral tool for workplace-based assessment (WBA) in forensic learning, providing real-time evaluation and feedback on students’ procedural competencies. This article delves into the usefulness, disadvantages, challenges, and implementation process of DOPS within forensic education. It includes practical examples to illustrate the impact of DOPS on enhancing the assessment process and preparing students for professional practice.